Pengaruh Penggunaan Strategi Pembelajaran Peningkatan Kemampuan Berpikir Terhadap Hasil Belajar Pada Mata Pelajaran Produk Kreatif dan Kewirausahaan di SMK Setia Darma Palembang - Aritia, Ildha; Lian, Bukman; Toyib, Muhammad (Journal of Innovation in Teaching and Instructional Media, 2022)
This study aims to determine whether there is an effect of using learning strategies to improve thinking skills on student learning outcomes at SMK Setia Darma Palembang by using experimental methods and the treatment design used in this study is Quasi Experimental Design. The population in this study were students of class XI Accounting at SMK Setia Darma Palembang, from 103 students 70 students were taken to be used as research samples. Data collection techniques are documentation, observation and tests. The effect of using learning strategies to increase thinking skills on learning outcomes in the subjects of creative products and entrepreneurship at SMK Setia Darma Palembang contributed 52.11% and the remaining 47.89% was influenced by other factors. From the results of data analysis, the average value of student learning outcomes in the experimental class was 83.42%, while the average value of learning outcomes obtained by the control class was 68.85%. This shows that there is an effect of using learning strategies to increase thinking skills on student learning outcomes at SMK Setia Darma Palembang.